2010
DOI: 10.1590/s0102-311x2010001000011
|View full text |Cite
|
Sign up to set email alerts
|

Medicine use among adolescents: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study

Abstract: IntroductionMedicines are an important therapeutic tool and an essential health resource, accounting for a significant part of the improvement in the population's quality of life and life expectancy. However, their irrational use poses direct and indirect risks to the population, while increasing the overall health costs and raising a highly relevant public health problem 1 .Medicine use is reaching high levels in both developed and developing countries. In Brazil, although the population has problems in acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…According to Moraes et al [6], in the city of Maringá, Brazil, 56% of the adolescents aged 14–18 years had used medicines in the previous 15 days; 53% used these medicines by self-medication, and the majority of these adolescents did not know the names of their medicines. Studies carried out in the city of Pelotas, Brazil, showed a high prevalence of medicine use among children and adolescents; 64% in children aged 1 year [7], 56% in those aged 3–4 years [8], and 31% in those aged 11 years [9]. Consistently, the literature indicates that the prevalence is higher among girls than boys [5,6,10,11].…”
mentioning
confidence: 74%
“…According to Moraes et al [6], in the city of Maringá, Brazil, 56% of the adolescents aged 14–18 years had used medicines in the previous 15 days; 53% used these medicines by self-medication, and the majority of these adolescents did not know the names of their medicines. Studies carried out in the city of Pelotas, Brazil, showed a high prevalence of medicine use among children and adolescents; 64% in children aged 1 year [7], 56% in those aged 3–4 years [8], and 31% in those aged 11 years [9]. Consistently, the literature indicates that the prevalence is higher among girls than boys [5,6,10,11].…”
mentioning
confidence: 74%
“…Only two other studies have compared medication use between obese and normal weight children: a study from a regional paediatric healthcare centre in Israel found about 60% more prescriptions in obese children between 12 and 18 years compared to normal weight children 38. Data from a follow-up of the Prevention and Incidence of Asthma and Mite Allergy (PIAMA) birth cohort at age 11 years in Brazil showed that obesity is associated with 20% higher intake of medications (prescription and OTC) 36. In contrast to the latter two studies, the present analysis was further able to examine which drug classes accounted for the differential between overweight and normal weight children.…”
Section: Discussionmentioning
confidence: 99%
“…para os sistemas nervoso e respiratório e os anti--inflamatórios 28,38 . Com relação às análises prospectivas de nosso estudo, embora algumas associações significativas tenham sido encontradas entre atividade física, o tempo de tela e o uso de medicamentos aos 18 anos, de um modo geral, os resultados não permitem confirmar inequivocamente a existên-cia de associação entre os comportamentos.…”
Section: Discussionunclassified
“…No entanto, quando as análises são estratificadas por sexo, a maioria das associações deixa de ser estatisticamente significativas. Possivelmente, a modificação nos resultados seja decorrente do fato de que meninas são, ao mesmo tempo, menos ativas e usam mais medicamentos 4,9,19,20,28 .…”
Section: Discussionunclassified
See 1 more Smart Citation